ARAHAN PRIORITAS PENANGANAN JARINGAN JALAN UNTUK PENGEMBANGAN EKONOMI DI DATARAN LORE KABUPATEN POSO - Megati, Yulius Christian; Ali, Amar Akbar; Suparman, Suparman (Katalogis, 2020)
This research aims to identify the location distribution of agricultural and tourism potential in the Lore plain of Poso regency, analyze the center of growth and the level of the regional hierarchy and prioritize the handling of road networks located in the Lore plain of Poso regency. This was a descriptive research. Analyses method used were descriptive analysis, Scalogram analysis, Gravitation analysis, and Analytical Hierarchy Process. The result of the research show that the agricultural potential is spread evenly across the villages in the Lore area and follows the existing road lines (the pattern extends the road). The spread of tourism potential is located in all sub-districts with the types of objects and tourism activities found in this area are natural attractions, special interest tourism activities and megalithic attractions. The result of Scalogram analysis shows that there are five villages that became the village center of growth, and the main priority in the handling of the existing road network is a network of roads connecting agricultural potential.